LEGAL PROTECTION OF FASHION DESIGN WITH MOTIFS IN THE DIGITAL ERA AGAINST COPYRIGHT INFRINGEMENT IN THE INDONESIAN FASHION - Sartika, Dewi; Mas, Elvi Yanti Dwi; Ekawati (Awang Long Law Review, 2025)
The introduction of digital technology into the process of creating and distributing fashion motif designs, such as the application of digital printing techniques, increasingly shows how vulnerable creative works are to copyright infringement practices. Learning and applying this technology also raises the need for adequate legal knowledge, so that there needs to be socialization and education regarding copyright among creative industry players. Along with globalization and increasingly widespread internet penetration, cases of copyright infringement are not limited to one country. The digital transformation in the fashion industry has opened up opportunities for designers to develop creative fashion motifs through digital media, but at the same time increases the risk of copyright infringement due to the ease of replication, distribution, and modification of designs online. The application of digital printing technology, for example, allows for the reproduction of motifs with high quality and speed that is difficult to monitor, thus raising legal issues if the design is duplicated without permission. The gap between advances in information technology and the legal framework for intellectual property protection and the low level of legal literacy among creative industry players further exacerbates this condition. Therefore, it is necessary to revise laws and regulations, improve monitoring mechanisms, and provide intensive education so that the copyright protection system for fashion motif designs can be comprehensively integrated. Integration between digital technology innovation and adaptive regulatory enforcement is considered the key to creating a fair, innovative fashion industry ecosystem that is able to provide proper rewards to creators.